Penggunaan Metode Blanded Learning Untuk Meningkatkan Pengetahuan Literasi Digital Mahasiswa Ilmu Komunikasi Fisip Universitas Mulawarman - Kheyene Molekandella Boer; Rina Juwita; Nurliah (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2023)
Digital literacy in Indonesia is an issue that continues to be promoted, considering that the government continues to encourage the improvement of communication and information technology infrastructure. Indonesia still has digital literacy competencies that fall into the